Relatório de Estágio Profissional "Aprender a Arte de ser Professor" - José Carlos Lemos Silva (2017)
The year in which the Professional Internship takes place is one of the mostimportant years in the life of a teacher, because it is the culmination of aprocess of exhaustive training and also the clash with reality. A year full of newlearning and new experiences capable of define much of what will be the way toteach in future years. My Professional Internship took place at the Francisco deHolanda Secondary School, located in the center of the city of Guimarães,which was for many years the Industrial School of the city and it´s now areference in education at national level. I was there with two other colleagueswho became friends and together we successfully surpassed all the challengesthat arose along the way. Thus, after a brief introduction comes the report,which in the way of reflection mirrors a little of what this adventure was. Idivided it into five chapters and the first one begins with my presentation, wherei also refer to what my previous experiences were and I also try to pass some ofmy essence in words. Then i make a legal, institutional and functionalcontextualization of what I consider most revealing in relation to the Internshipand where I also present the school context where I was inserted. Theserepresent the first and second chapters of this document and are respectivelythe "Personal Framing" and the "Professional Framework". The next chapter isreally the core of the work where I refer all the relevant aspects of myprofessional practice as a teacher, describing and reflecting on everything thatmade me grow throughout this year. This chapter is called "Realization ofProfessional Practice". The fourth chapter is a little different from itspredecessors because here I present my research that focused on a case studyabout the impact of a functional training program on the levels of physicalfitness, self-esteem and self-perception of a student who is sick cancer. Finally,the fifth chapter concerns the final reflection and my prospects for the future.